THE EFFECT OF TAX AVOIDANCE, ESG, AND POLITICAL CONNECTION ON FIRM VALUE 2021-2023 - Sadjiarto, Arja; Karistianto, Kalef; Tjandra, Putri Meydelin (UPT Publikasi Ilmiah UNISBA, 2024)
This study aims to investigate whether tax avoidance, ESG, and political connections affect firm value under current conditions. The purpose of this research is to examine the effects of tax avoidance, ESG, and political connections on firm value. Data analysis was conducted using Gretl. The sample consists of publicly traded non-financial companies from 2021 to 2023. The study uses a purposive sampling technique, resulting in 159 observations. This quantitative research utilizes multiple linear regression. Data was obtained from the Refinitiv Database and Annual Reports. The results show that ESG and tax avoidance significantly affect firm value, whereas political connections do not have an impact on firm value. The expected contribution of this research is to enhance transparency among all stakeholders, demonstrating the company’s commitment to tax compliance, ESG, implementation, and corporate governance, thereby increasing firm value. Keywords : ESG, Firm Value, Political Connection, and Tax Avoidance